Observation of the effect of thiobencarb herbicide on three species of fresh water fish - Mohamad, Rosli; Omar, Dzolkhifli (1989)
An experiment was conducted in glass tanks to observe the effect of thiobencarb herbicides on several fresh-water fishes. Three species on fish, Oreochromis mossambicus/0. niloticus (Tilapia merah), Clarias batrachus (Keli) and Punctius gonionotus (Lampam jawa, aged about 1.5 months old, were exposed to granular thiobencarb herbicide at the recommended rate of application to the field. Observations on the behaviour changes and mortality showed that symptoms of abnormal swimming activities occured within 1h after exposure. However, P. gonionotus recovered and survived until 48h of observation period, whereas, mortality of 100% and 87% were recovered for C. batrachus and 0. mossambicus/0. niloticus, respectively.